Quantification of beam steering with an ionization chamber array. (25th March 2018) - Gao, Song; Balter, Peter A.; Tran, Benjamin; Rose, Mark; Simon, William E.
Abstract: Routine quality assurance for linear accelerators (linacs) usually involves verification of beam steering with a water scanning system. We established a beam steering procedure that uses a 2D ionization chamber array (ICA) and verified the equivalence of beam symmetry between the ICA and a water scanning system. The ICA calibration accuracy, reproducibility and stability were evaluated and the uncertainty in the measurement of beam symmetry due to the array calibration was examined. Forty‐five photon beams and 80 electron beams across 7 Varian C‐series and 4 TrueBeam linacs were steered in the radial and transverse directions using an ICA. After beam steering, profiles were re‐measured using the ICA and in‐water using a 3D Scanner (3DS). Beam symmetries measured with the ICA and 3DS were compared by (a) calculating the difference in point‐by‐point symmetry, (b) plotting the histogram distribution of the symmetry differences, and (c) comparing ICA and 3DS differences with their respective Varian symmetry protocol analysis. Array calibrations from five different occurrences (2012 to 2016) over six different beams reproduced within 0.5%. The uncertainty in beam symmetry was less than 0.5% due to the uncertainties in the array calibration. After all beams were steered using the ICA, the point‐by‐point symmetry differences between ICA and 3DS at the off‐axis positions of 20% and 80% of field size for all beam profiles indicated that 95% of point‐by‐point symmetry comparisons agreed within 0.7%, and 100% agreed within 1.0%; after steering with the ICA 97.8% of photon beam profiles (88 of 90) and 97.5% of electron beam profiles (156 of 160) had symmetry within 1% when measured with the 3DS. All photon and electron beam profiles had symmetry within 1.1% and 1.2%, respectively, for profiles measured with the 3DS. Our data demonstrate that a calibrated ICA can be used to steer photon and electron beams achieving beam symmetry within 1% when re‐measured with a 3D water scanning system.